Konzept - Kunst. - Kunstmuseum Basel; Felix, Zdenek; Harrison, Charles; Honnef, Klaus (Basel : Kunstmuseum Basel, 1972)
Art & Language ; Baldessari, John ; Barry, Robert ; Bochner, Mel ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Darboven, Hanne ; Dibbets, Jan ; Gilbert & George ; Haacke, Hans ; Huebler, Douglas ; Kawara, On ; Weiner, Lawrence
biog., bibliog. per kunstenaar
"Konzept" - Kunst, Kunstmuseum Basel, 18. März - 23. April 1972
Duits
Engels
boek